Expression Analysis and Functional Characterization of CER1 Family Genes Involved in Very-Long-Chain Alkanes Biosynthesis in Brachypodium distachyon - Wu, Hongqi; Shi, Shandang; Lu, Xiaoliang; Li, Tingting; Wang, Jiahuan; Liu, Tianxiang; Zhang, Qiang; Sun, Wei; Li, Chunlian; Wang, Zhonghua; Chen, Yaofeng; Quan, Li (Frontiers in Plant Science, 2019)
Cuticular wax accumulation and composition affects drought resistance in plants. Brachypodium distachyon plants subjected to water deficit and polyethylene glycol (PEG) treatments resulted in a significant increase in total wax load, in which very-long-chain (VLC) alkanes were more sensitive to these treatments than other wax compounds, implying that VLC alkanes biosynthesis plays a more important role in drought resistance in Brachypodium distachyon. ECERIFERUM1 (CER1) has been reported to encode a core enzyme involved in VLC alkanes biosynthesis in Arabidopsis (Arabidopsis thaliana), but few corresponding genes are investigated in Brachypodium distachyon. Here, we identified eight CER1 homologous genes in Brachypodium distachyon, namingly BdCER1-1 to BdCER1-8, and then analyzed their sequences feature, expression patterns, stress induction and biochemical activities. These genes had similar protein structure to other reported CER1 and CER1-like genes, but displayed closer phylogenetic relationship to the rice OsGL1 genes. They were further found to exhibit various tissue expression patterns after being induced by abiotic stresses. Among them, BdCER1-8 gene showed extremely high expression in leaves. Heterologous introduction of BdCER1-8 into the Arabidopsis cer1 mutant rescued VLC alkanes biosynthesis. These results indicate that BdCER1 genes are likely to be involved in VLC alkanes biosynthesis of Brachypodium distachyon. Taken together, BdCER1-8 seems to play an explicit and predominant role in VLC alkanes biosynthesis in leaf. Our work provides important clues for further characterizing function of CER1 homologous genes in Brachypodium distachyon and also an option to improve drought resistance of cereal crops.